2020
DOI: 10.3390/su12073025
|View full text |Cite
|
Sign up to set email alerts
|

Mediating Effects of Cohesion Policy and Institutional Quality on Convergence between EU Regions: An Examination Based on a Conditional Beta-Convergence Model with a 3-Way Multiplicative Term

Abstract: The paper contributes to the existing literature on the EU's Cohesion Policy outcomes by extending the conditional beta-convergence model with a 3-way multiplicative term to examine the mediating effects of the Cohesion Policy, institutional quality, and their interaction on regional convergence. The empirical analysis based on conditional slope coefficients and conditional standard errors provides evidence that both the mediating factors under consideration contribute positively to boosting regional convergen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 61 publications
(135 reference statements)
1
3
0
Order By: Relevance
“…As expected, the estimations revealed that conditional beta convergence between EU NUTS 2 regions is present. It is in line with Bisciari, Essers & Vincent [31], Butkus, Mačiulyt ė-Šniukien ė & Matuzeviči ūt ė [32], Cartone, Postiglione, & Hewings [33] findings. However, regional economic disparities are still substantial [11], and the rate of convergence is slow.…”
Section: Discussion and Policy Implicationssupporting
confidence: 89%
“…As expected, the estimations revealed that conditional beta convergence between EU NUTS 2 regions is present. It is in line with Bisciari, Essers & Vincent [31], Butkus, Mačiulyt ė-Šniukien ė & Matuzeviči ūt ė [32], Cartone, Postiglione, & Hewings [33] findings. However, regional economic disparities are still substantial [11], and the rate of convergence is slow.…”
Section: Discussion and Policy Implicationssupporting
confidence: 89%
“…Following Wright (1976), Friedrich (1982), and Leona and West (1991), it can be argued that not just the slope of gr i,t→T on F i,t varies depending on the values of D i,t , I i,t and their interaction, i.e., I i,t D i,t , as Equation (3) shows, but also the standard error associated with this slope. According to Butkus et al (2020), the standard error of the estimated composite term…”
Section: Methodsmentioning
confidence: 99%
“…As Banerjee, Duflo & Qian (2020) and Chen et al (2021) mentioned, TI inequality leads to negative consequences such as inefficient allocation of resources, knowledge spill-over interruption, and market vulnerability. The efficiency of investment allocation could depend on the institutional quality (Butkus et al, 2020). The distribution of funds for TI projects is mainly influenced by corruption.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…where expression in the brackets shows that the effect of TII on growth is conditional and depends on the level of TII and control of corruption simultaneously. The formulae for calculating standard errors associated with this conditional slope coefficient can be found in Butkus et al (2020).…”
Section: Model and Datamentioning
confidence: 99%